The role of filamentous fungi in drinking water biofilm formation - Chaves, Ana F. A. (2020)
The presence of biofilms in drinking water distribution system (DWDS) constitutes one of the currently recognized hazards affecting the microbiological quality of drinking water (DW). Also, biofilms can alter the taste, odor, and the visual appearance of water, which is an indication of poor DW quality and may lead to a number of unwanted effects on the quality of the distributed water. Very few reports on filamentous fungi (ff) biofilms can be found in the literature mainly because these fungi do not conform completely to the biofilm definitions that are usually proposed for bacteria. Nevertheless, filamentous fungi are microorganisms that due to their (1) absorptive nutrition mode, (2) secretion of extracellular enzymes to digest complex molecules, and (3) apical hyphal growth that form lattices, which are excellent candidates for biofilm formation. However, this aspect is still poorly understood. In several environments, bacteria and ff cohabit and interact with each other, which has a wide range of applications and influences both organisms, sometimes creating an increase in resistance to antibiotics and antifungal agents. This chapter provides an overview on the presence of ff in DWDS, including their interaction with bacteria and potential biofilm formation.